Media Sosial dan Promosi Perpustakaan Berbasis Media Digital - Gufroni, Aan (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2022)
This study discusses the use of social media as a means of promoting student interest in reading at the IAIN Metro Library. The purpose of this study was to determine the use of social media in the promotion of student interest in reading carried out by the library. This study uses a descriptive research method with a qualitative approach. Data was collected through observation, interviews, documentation and literature review and then processed by data analysis techniques. The results of this study indicate that the library uses social media Instagram and Facebook to promote the library and the importance of students' interest in reading. Social media features have been fully utilized, but the library's social media admins have not used all of these features in accordance with the results of the best practice of experts, so there are some that have not been utilized.